Antioxidant Properties of Organostibines Against Lipid Peroxidation in Homogenized Rat Brain - De Jesus Hernandez Silva, Maria; Luengas, Elizabeth; Sharma, Manju; Nieto Camacho, Antonio; Vazquez, Jaime; Rodriguez Castillo, Luis; Sharma, Pankaj; Gutierrez, Rene (Asian Journal of Chemistry, 2013)
The effect of six different synthesized organoantimony compounds viz. tris-(3-methyl-2-thienyl)stibine (1), tris-(5-chloro-2-thienyl) stibine (2), tris-(2-selenophenyl)stibine (3), chloro-bis(N,N-dimethyl-(1-ferrocenylethyl amine)Sb(III) (4), tris-(2-dimethyl aminoethyl ferrocenyl)stibine (5), 1-(2-diphenylstibine-ferrocenyl)methyldimethylamine (6) on thiobarbituric acid reactive species (TBARS) production, free radical activity in the rat brain homogenate were determined. Their antioxidant activity were compared with the quercetin, Butylated hydroxytoluene (BHT; 2,[6]-di-tert-butyl-pcresol) and a-tocopherol as reference antioxidants. All compounds showed a dose dependent inhibition on TBARS production. Tris-(5-chloro-2-thienyl)stibine (2) showed lipid peroxidation inhibition in homogenized rat's brain, double in magnitude, than shown by tris-(3-methyl-2-thienyl)stibine (1) activity. The compound (2) showed a reduction of > 80 % of DPPH radical reduction while the compound 1 did not show a significant antioxidant activity. Variety of simple organo antimony compounds display antioxidant activity in vitro against TBARS production, however detailed toxicological studies must be carried out with stibines in order to determine whether these compounds could be tested therapeutically as an antioxidant.